SMEs within a data-driven sustainable finance framework: A European survey - Felix Rossmann; Jan Greitens; Lisa Knoll (Goethe University Frankfurt, Center for Financial Studies (CFS), 2025)
Sustainable finance regulations and initiatives across Europe have predominantly targeted large corporations, while small and medium-sized enterprises (SMEs) are increasingly drawn into the framework, often facing challenges such as resource constraints and complex documentation requirements. To capture the dynamics of this field, a European survey conducted in 2025 with responses mainly from German and Austrian companies examined SME engagement with sustainable finance. The findings show a rising share of SMEs investing in sustainability in comparison to the preceding study in 2023, with internal funding as the dominant source. Where external financing is used, it is primarily activated on publicly supported bank loans, whereas capital markets remain largely irrelevant for SMEs. While a connection between sustainability data collection and sustainable investment exists, many SMEs invest without systematically collecting data. These results highlight the continued centrality of traditional banking relationships as the main external financing channel for SMEs, which could serve to enable and facilitate capital flows toward sustainability rather than prescribe or direct them.
Keywords: 330; Sustainable Finance; Small and Medium-sized Enterprises; Sustainability Investment; Sustainability Reporting; Bank Financing